The COMPARISON OF SHARIA BANKING PERFORMANCE IN INDONESIA AND MALAYSIA REVIEWING FROM MAQASHID SHARIA INDEX - Alfadri, Ferri Alfadri (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
The purpose of this study was to determine whether there is a difference in the performance of Islamic banks in Indonesia and Malaysia on the Maqashid Syariah Index. This study was a quantitative study using the independent samples t-test for comparative analysis. The study targets 8 Indonesian Islamic Commercial Banks and 8 Malaysian Islamic Banks. The data type used is the secondary data in the form of 2021 company financial statements obtained from the official websites of each bank. The research sampling method adopts purposeful sampling. The results showed that Indonesian and Malaysian Islamic banks did not differ in their performance in terms of educational goals, and Indonesian and Malaysian Islamic banks differed significantly and significantly in their performance in achieving justice. There was no significant difference in the performance of Islamic banks in Indonesia and Malaysia.Malaysia is viewed from the public interest. And there is a significant difference between the performance of Islamic banking in Indonesia and Malaysia in terms of the Maqashid Syariah Index (MSI).